The use of formalist techniques and semiotic analysis in depicting social media realities in 'budi pekerti': a study of cinematic composition and social commentary - Rizkitaa, Meira Rai; Supiarza, Hery; Pawitan, Zakiah (Gelar: Jurnal Seni Budaya, 2024)
The film "Budi Pekerti" has garnered critical acclaim, earning multiple awards and nominations at prominent festivals, including the Toronto International Film Festival 2023 and Jakarta Film Week 2023. This study examines how cinematic techniques are utilized to depict social realities. Anchored in Sergei Eisenstein's formalist theory and Roland Barthes' semiotic analysis, the research adopts a qualitative methodology involving scene observations, in-depth interviews with the director, and document analysis. The findings reveal that montage techniques and visual compositions effectively construct narratives that highlight moral and ethical issues. Additionally, the use of symbols within the film uncovers culturally relevant messages, providing deeper insights into contemporary social dynamics. Through an integrative approach combining formalist and semiotic perspectives, the study underscores the critical role of cinematic aesthetics in conveying complex social commentaries. This research makes a significant contribution to the fields of visual arts, communication, and linguistics by offering a comprehensive framework that links visual storytelling with cultural critique and societal reflection, emphasizing the power of film as a medium for understanding and shaping cultural narratives.